2020
DOI: 10.1177/1741143220942527
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of problems and challenges faced by school leaders (2003–2019)

Abstract: The purpose of this scoping review is to analyse the literature concerning principals’ problems and challenges, beginning in 2003 and ending in 2019. The research team conducted an extensive search to locate relevant academic literature, comprising 17 years of research, and a total of 153 documents were analysed. According to the findings, most of the documents (71%) correspond to the last six years (2014–2019), and most are studies from Anglo-Saxon countries (55%). The results point to eight main categories r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 121 publications
2
39
0
Order By: Relevance
“…The results of the current study are in line with the principals' health and wellbeing surveys conducted in Australia, New Zealand, Ireland and Finland (Riley, 2015(Riley, , 2017(Riley, , 2020Trade Union of Education in Finland, 2020), which showed that regardless of the cultural differences and diversity in the school systems, the size of the principals' workloads and the lack of time to focus on teaching and learning were two main causes of their stress in all four countries. This suggests that principals' occupational stress is, to some extent, a universal phenomenon (see also Tintore et al, 2020). In addition to high workloads, principals are struggling with interpersonal conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study are in line with the principals' health and wellbeing surveys conducted in Australia, New Zealand, Ireland and Finland (Riley, 2015(Riley, , 2017(Riley, , 2020Trade Union of Education in Finland, 2020), which showed that regardless of the cultural differences and diversity in the school systems, the size of the principals' workloads and the lack of time to focus on teaching and learning were two main causes of their stress in all four countries. This suggests that principals' occupational stress is, to some extent, a universal phenomenon (see also Tintore et al, 2020). In addition to high workloads, principals are struggling with interpersonal conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…As Fullan (2020) states, "complexity means change, but specifically it means rapidly occurring, unpredictable, nonlinear change" (p. ix). Although school leaders have always been dealing with concurrent and heterogeneous challenges (Tintoré, Cunha, Cabral, & Alves, 2020) the COVID-19 pandemic has significantly and rapidly put them into a complex situation that seems to last or have long-term consequences. And this complexity will persist.…”
Section: Discussionmentioning
confidence: 99%
“…Next, leadership effectiveness may vary with school grade levels because of different curricular foci (Burcar, 2017). Third, the effectiveness of leadership practices may vary in schools of different performance levels because of students' diverse learning needs (Tintore et al, 2020). Lastly, leadership effectiveness may vary with leaders' school hierarchical position (Connolly et al, 2019).…”
Section: Moderating Variablesmentioning
confidence: 99%